Nanoparticles in Cancer Treatment: Physics Principles and Therapeutic Applications - Satoory, Ahmed Khudair; Sadoon noory, Tabarik; Ayad Ali, Zaidoun; Abbood, Ayat Abd_UL hussein; Jasem, Zainab Abbas (American Journal of Botany and Bioengineering, 2024)
The use of nanomaterials in cancer therapy is an example of promising enhanced therapeutic ability, particularly in the diagnostic and drug delivery fields. Tumor treatment using magnetic particles in hyperthermia methods was also proposed. All those treatment possibilities, in relation to normal surgical and/or chemotherapeutic approaches, provide distinct advantages like minimal invasiveness, spatial and temporal treatment selection, simultaneous imaging, and selective treatment, i.e., allowing treatment only on the cancer-affected tissue while the healthy tissue remains unchanged. The tissue imaging followed by the therapy can increase the success rate, decrease the possibility of life-treated part malfunction, and represents a major advantage to the use of nanoparticles properly conjugated with the right molecule. Typically, the process that a nanoparticle undergoes inside the human body starts with intravenous injection, signaling to a specific compound within the blood vessel to link to it and transport it to the targeted location. Here, the nanoparticle-conjugated specific molecule can release drugs or be activated by an external agent or suffer from a distortion of its characteristics. The visualization of whether there is a tumor presence is always necessary. A diagnosis followed by chemotherapy or surgery brings the excellent possibility of eliminating the tumor. [1] [1][2][3]